INTEGRATING ENVIRONMENTAL EDUCATION AND SOCIAL INCLUSION: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE LEARNING - Bento, Yara Rosa Mattos; Duarte, Luis Felipe de Almeida (Seven Editora, 2025)
Integrating Environmental Education into basic education is vital to fostering critical, sustainability-oriented citizenship. Active and interdisciplinary approaches enhance inclusion and environmental literacy, though limited resources and teacher training remain key challenges. Thus, this study aims to analyze how environmental education and social inclusion are integrated into basic education, identifying global strategies, national approaches, and challenges for achieving sustainable and inclusive learning through an integrative literature review. An integrative literature review was conducted using SciELO, CAPES, and official documents from the UN, UNESCO, MEC, BNCC, and CNE. Studies published between 2000 and 2025 were analyzed, focusing on recent discussions on environmental education, social inclusion, and the SDGs. Critical and interdisciplinary approaches guided the selection, enabling the identification of theoretical trends and challenges in integrating Environmental Education into basic education. The results show that integrating Environmental Education with Inclusive Education is essential to strengthen democratic and sustainability-oriented public schools. Interdisciplinary practices, accessible technologies, and partnerships between schools, communities, and public policies enhance meaningful learning and socio-environmental citizenship. However, progress in this integration depends on continuous teacher training, institutional support, and the effective inclusion of environmental themes in school curricula. It is recommended to reinforce education policies aligned with the SDGs to consolidate a sustainable, equitable, and transformative basic education system. DOI: https://doi.org/10.56238/sevened2025.038-031